2021
DOI: 10.1002/acg2.113
|View full text |Cite
|
Sign up to set email alerts
|

Immunological tumor heterogeneity and diagnostic profiling for advanced and immune therapies

Abstract: Immunotherapies have changed the way how we treat cancer at all stages. The understanding of the immune system in individual tumor specimens guides the selection of immune-modulating agents such as immune checkpoint inhibitors alone or in combination with other therapeutic agents that target, modulate or unleash the patient's immune system. Despite the similar histopathological diagnosis, each tumor is unique at its primary site and site of metastasis, also depending on previous treatment regimens or genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…However, the TEAL model predicts, for adaptive threats in an excluded pro-tumor IME, the emergence of an unstable state, resulting in either accrual or depletion of TAAs in a manner that depends on the current TAA abundance. This splitting behavior into ‘hot’ and ‘cold’ tumors offers insight into the microenvironmental features generating spatial immunogenic diversity within solid tumors and is consistent with prior observations ( Huss et al, 2021 ; Jia et al, 2022 ; Meiller et al, 2021 ; Lakatos et al, 2020 ). This argues that TAA-depleted tumors share in common the tendency for their evasion strategies to incur less antigenic penalties.…”
Section: Discussionsupporting
confidence: 88%
“…However, the TEAL model predicts, for adaptive threats in an excluded pro-tumor IME, the emergence of an unstable state, resulting in either accrual or depletion of TAAs in a manner that depends on the current TAA abundance. This splitting behavior into ‘hot’ and ‘cold’ tumors offers insight into the microenvironmental features generating spatial immunogenic diversity within solid tumors and is consistent with prior observations ( Huss et al, 2021 ; Jia et al, 2022 ; Meiller et al, 2021 ; Lakatos et al, 2020 ). This argues that TAA-depleted tumors share in common the tendency for their evasion strategies to incur less antigenic penalties.…”
Section: Discussionsupporting
confidence: 88%
“…However the TEAL model predicts, for adaptive threats in an excluded pro-tumor IME, the emergence of an unstable state resulting in either accrual or depletion of TAAs in a manner that depends on the current TAA abundance. This splitting behavior into 'hot' and 'cold' tumors offers insight into the microenvironmental features generating spatial immunogenic diversity within solid tumors and is consistent with prior observations (Huss et al, 2021;Jia et al, 2022;Meiller et al, 2021;Lakatos et al, 2020). This argues that TAA-depleted tumors share in common the tendency for their evasion strategies to incur less antigenic penalties.…”
Section: Discussionsupporting
confidence: 88%
“…Especially for advanced therapeutics (cell-and gene therapy) it is the only path towards a statement on the prognosis and possible predictions for the most effective treatment. 54 A significant number of relevant biomarkers including proteins and genetic alterations have already been identified which guide therapeutic strategies and decisions in many tumor entities. 55 Galon et al 56 demonstrated that the combination of two spatially resolved immune cell markers in different cancer tissue compartments show a better predictive value than each single marker alone.…”
Section: Analysis Of Immune and Tumor Heterogeneitymentioning
confidence: 99%
“…Both and in particular their spatial co-existence have a significant prognostic value and need be included in therapeutic considerations. [103][104][105][106] • Multiplex immunohistochemistry 23,24,49,51 • Whole sllide imaging 5 • Image analysis 27,43 • PD-L1 quantification 72,94,95,99 • Large date extraction 22 • Multidimensional data analysis 31,48,49 • Mutation detection and analysis 6,89,107 • Spatial transcriptomics 41 • Drug development 36 Digitale Biomarker • Disease diagnosis 2 • (Tumor) Immune infiltrates 58,73 • Prognostic biomarker 30,105,106 • Personalized medicine and response prediction 23,42,47 • Cell-and Gene therapy 54,68 • IO/non-OI combination therapies 55,64,70,77 • Immune escape prediction 63,64 • Metastases assessment 39,74,98 F I G U R 1 Simplified scheme the proposed path from a regular diagnostic pathology workflow to delivering a precision oncology approach through the AI-supported application of digital biomarker that allow the best possible resp...…”
Section: Artificial Intelligencementioning
confidence: 99%